Differences in income, farm size and nutritional status between female and male farmers in a region of Haiti - Duvivier, Predner; Tescar, Robers Pierre; Halliday, Cassandra; Murphy, Madhuvanti M.; Guell, Cornelia; Howitt, Christina; Augustus, Eden; Haynes, Emily; Unwin, Nigel (Frontiers in Sustainable Food Systems, 2024)
Haiti is the poorest country in the Americas and has the highest levels of gender inequality. It has high burdens of malnutrition and food insecurity. Our aim in this study was to investigate differences between female and male heads of farms in their farm's size and income and in their nutritional status. We conducted a mixed-method study with a quantitative survey with 28 female and 80 male farmers and qualitative semi-structured interviews with seven women and 11 men, in nine rural communities, Plateau de Rochelois, Nippes, Haïti. We found that significant inequalities existed between female and male heads of farms in this region of Haiti. Farm income was associated with farm size, with female farmers having on average smaller farms, and markedly lower farm incomes compared to male farmers, even after adjusting for the fact that their farms were smaller. Male farmers also had more access to seeds, financing and transportation to market. In addition, female farmers had markedly higher levels of overweight and obesity. In both male and female heads of farms around 1 in 20 were underweight. These findings complement those from other settings, showing that female farmers in low-and middle-income countries typically face severe challenges in accessing resources such as land, credit, and inputs, which can limit their productivity and incomegenerating potential. Gender sensitive interventions to promote farmer health, well-being and productivity are required.